2021
DOI: 10.1002/ctm2.289
|View full text |Cite
|
Sign up to set email alerts
|

A potent and selective small molecule inhibitor of myoferlin attenuates colorectal cancer progression

Abstract: As a pivotal vesicular trafficking protein, Myoferlin (MYOF) has become an attractive target for cancer therapy. However, the roles of MYOF in colorectal cancer invasion remain enigmatic, and MYOF‐targeted therapy in this malignancy has not been explored. In the present study, we provided the first functional evidence that MYOF promoted the cell invasion of colorectal cancer. Furthermore, we identified a novel small molecule inhibitor of MYOF (named YQ456) that showed high binding affinity to MYOF (KD = 37 nM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
(102 reference statements)
0
16
0
Order By: Relevance
“…The expression of this protein correlates with a poor survival in PDAC patients [ 2 , 3 ], and we reported the inability of PDAC cells to migrate and implant in the liver when myoferlin expression is inhibited [ 27 ]. Recently, three innovative compounds have been described for their ability to bind to myoferlin and reduce the metastatic dissemination of breast [ 10 ], colon [ 12 ], and pancreas [ 11 ] cancers, demonstrating its pharmacopotential. In this study, we described that WJ460, a small compound binding to myoferlin, induced the same main biological effects as myoferlin gene silencing in several PDAC cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of this protein correlates with a poor survival in PDAC patients [ 2 , 3 ], and we reported the inability of PDAC cells to migrate and implant in the liver when myoferlin expression is inhibited [ 27 ]. Recently, three innovative compounds have been described for their ability to bind to myoferlin and reduce the metastatic dissemination of breast [ 10 ], colon [ 12 ], and pancreas [ 11 ] cancers, demonstrating its pharmacopotential. In this study, we described that WJ460, a small compound binding to myoferlin, induced the same main biological effects as myoferlin gene silencing in several PDAC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the contribution of mitochondria to cancer development and progression has become firmly established [ 9 ], and our recent studies indicate that myoferlin could be a valuable target for new therapeutic strategies. This aspect appears increasingly pertinent as pharmacological compounds targeting myoferlin were recently described [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Another 1,5‐diaryl‐1,2,4‐triazole derived compound named YQ456 blocked the associations between MYOF and RAS‐related binding proteins and thereby inhibited the growth and invasion of colorectal cancer (Figure 12). 310 These findings demonstrated that targeting MYOF with small‐molecule inhibitors is a prospective therapeutic method for reversing EMT process and blocking tumor metastasis in MYOF‐driven cancers. Efforts should be made to discover more potent compounds that interfere with MYOF, and deeper studies will focus on the clinical application of these MYOF inhibitors.…”
Section: Drug Discovery Strategies Targeting the Key Proteins Involve...mentioning
confidence: 93%
“…TRRAP has been found to be involved in the regulation of stemness in ovarian cancer stem cells (35), while DNMT1 and EPHB1 can regulate tumor progression (38,46). Other genes have been reported to been involved in the control of proliferation, invasion, and apoptosis in cancer cells (36,37,(49)(50)(51)(52)(53)(54)(56)(57)(58)(59).…”
Section: Genomic Profiling In Osccmentioning
confidence: 99%